KEPUASAN HUBUNGAN ANTARA DETERMINASI DIRI TERHADAP PENYESUAIAN DIRI PADA BINTARA REMAJA DI DITSAMAPTA - Alice Zellawati; Laila Shofatin Nimah; Brigitan Argasiam (IMAGE, 2021)
This research aims to determine the relationship between self-determination and self-adjustment among Youth Non-Commissioned Officers at the Central Java Regional Police Ditsamapta. The population in this study were all members of the Central Java Regional Police Ditsamapta youth non-commissioned officers, totaling 115 people. The sampling technique used was purposive sampling. The sample size was 85 people because 30 were female teenage non-commissioned officers (Polwan). Data analysis in this study used Spearman correlation analysis. This research uses a psychological scale data collection method in the form of a Likert scale which consists of two scales, namely, a 24-item self-determination scale (? = 0.957) and a 24-item self-adjustment scale (? = 0.963). Based on the hypothesis proposed, namely "There is a positive relationship between self-determination and individual self-adjustment", it can be accepted. This is shown by the significance value = 0.000, which means that the self-determination variable has a significant effect on individual self-adjustment, while the positive value of the Spearman coefficient rs = +0.915 indicates that the higher the individual's self-determination, the higher the self-adjustment, conversely, the lower the determination. the self they have, the lower their self-adjustment will be. Meanwhile, the effective contribution value of the self-determination variable to self-adjustment is 85.2%, while the remaining 14.8% is influenced by other factors. Keywords: Self-Adjustment, Self-Determination